India : Financial Sector Assessment Program-Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2018)
This report evaluates the Observance of the Basel Core Principles for Effective Banking Supervision in India. It highlights that the supervision and regulation by the Reserve Bank of India remain strong and have improved in recent years. A key achievement is implementation of a risk-based supervisory approach that uses a complex supervisory assessment framework to guide the intensity of supervisory actions and the allocation of supervisory resources. Also, most of the Basel III framework has been implemented and cooperation arrangements, both domestically and cross-border, are now firmly in place. The system-wide asset quality review and the strengthening of prudential regulations in 2015 testify to the authorities' commitment to transparency and a more accurate recognition of banking risks.